A Systematic Literature Review on Communication In Health Using Narrative Theory - Rizky Amalia Wismashanti; Irwansyah Irwansyah; Kianti Azizah; Sugiarto Sugiarto (Universitas Bina Sarana Informatika, 2023)
This article is structured to find out the use of Narrative Theory in the current context of health communication. The main question discussed is: how is the application of Narrative Theory in the context of health communication in the last four years. For answering this research problem using qualitative methode, a study based on a systematic literature review was conducted. The research was conducted using Preferred Reporting Items for Systematic narrative theory, communication in health (Results) Narrative theory in the context of health is considered to function effectively to prevent disease. This is because a delivery with this narrative is easier for people to remember. In addition, the narrative is also used to help the healing process by placing narration as a vessel to express one's feelings. The narrative is also considered motivating in managing emotions for healing. The use of narrative in the patient's healing process does not stand alone but is used as a complement to the healing process, in addition to medication and physical therapy. Currently, narratives can be mediated digitally. The conclusion from this study, further research and directions are needed regarding communication in the health context using Narrative Theory.